(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
In this article, an important part of mathematical control theory one of the directions in the theory of differential games pursuit-evasion problems were posed in simple differential games with constraints. Pursuit problem and escape problems were solved. Solution of the capture problem by the theorem is proven.